Preparation of polycation with hydroxyls for enhanced delivery of miRNA in osteosarcoma therapy. (21st April 2022) - Chen, Da-Fu; Zhang, Bo-Wen; Cao, Jingjing; Wang, Honggang; Luo, Peng; Liu, Weifeng; Niu, Xiaohui; Wang, Renxian; Nie, Jing-Jun
Abstract : Ethanolamine-decorated poly(glycidyl methacrylate) (PGMA) polycation with abundant hydroxyl groups, namely PGEA, was proposed as a safe and effective miRNA delivery system for the treatment of osteosarcoma. Abstract : Osteosarcoma, a malignant bone tumor that usually occurs in children and adolescents, has a high rate of death and disability, bringing great pains to society and families. Improving treatment approaches for osteosarcoma patients remains a constant and major goal for researchers and clinical groups due to the limited therapeutic efficiency and survival rate. MiRNAs have been reported to play a crucial role in osteosarcoma occurrence, progression, and metastasis, which provides a new insight for osteosarcoma therapy. In other words, the intervention of the involved miRNA may be a promising way for osteosarcoma. In this study, we developed ethanolamine (EA)-decorated poly(glycidyl methacrylate) (PGMA) polycations (termed as PGEAs) to deliver miR-223 for osteosarcoma inhibition. The introduced hydroxyl groups via EA modification in the PGEA vector can form a hydration shell, hinder protein adsorption, and help the PGEA-based delivery system escape from the in vivo clearance, which further benefits the accumulation of the delivery system in the tumor area. A series of in vitro anti-tumor assays illustrate that the PGEA-2 vector can efficiently deliver miR-223 into osteosarcoma cells for impressive anti-tumor effects via inhibiting malignant behavior of osteosarcoma cells, including proliferation, migration, and invasion. Osteosarcoma inhibition assays in vivo further confirmed the anti-tumor efficiency of PGEA-2/miR-223 complexes without inducing evident toxicity. This work will help develop miRNA for osteosarcoma therapy, and the proposed PGEA based delivery system also provides a promising and safe strategy for gene therapy of osteosarcoma.